Model Kolaboratif Dalam Meningkatkan Efektivitas Pengelolaan Pembiayaan Pendidikan Di MTs Negeri 3 Sleman Yogyakarta - Aji, Handaru Baskara; Azizah, Rosa Kamelia; Shaleh (Journal of Practice Learning and Educational Development, 2025)
Education financing is an important factor in supporting the success of learning in schools. Effective and efficient financing management can improve the quality of education. This research uses descriptive qualitative methods. Informants, including the Principal, Head of Administration, and Treasurer, are the parties involved in policy making and budget management at the school. The instruments used in this research were interview guidelines and documentation in accordance with the research objectives. Data analysis uses the Miles, Huberman, and Saldana model, which involves data condensation, data presentation, and verification to draw conclusions. The results of this research are financing management at MTs Negeri 3 Sleman Yogyakarta which involves three main models: Flat Grant Model, The Resources Cost Model, and Historic Funding Model. Allocation and use of funds is carried out strategically, among others: identifying needs, determining priorities, transparent and accountable management, long-term planning through strategic plan, as well as evaluating and periodically adjusting the budget. Monitoring and control of financing management is carried out as follows. Monitoring is carried out through periodic financial audits, routine financial reports, use of the financial management information system, periodic evaluations, and determination of financial performance indicators that focus on the quality of planning, implementation, and results. Control and prevent errors in budget use, implements mechanisms such as structured budget planning, document verification procedures, periodic monitoring, and transparency through the publication of financial reports. This research focuses on an effective education financing management model to improve the quality of education at MTs Negeri 3 Sleman, Yogyakarta.